Traumatic Brain Injury-Related Optic Nerve Damage. Issue 5 (23rd April 2022) - Qiu, Jianhua; Boucher, Masen; Conley, Grace; Li, Yue; Zhang, Jingdong; Morriss, Nicholas; Meehan III, William P; Mannix, Rebekah
Abstract: Vision disorders are associated with traumatic brain injury (TBI) in 20%–40% of clinical cases and involve a diverse set of potential symptoms that can present acutely or chronically. Due to its structure and position, the optic nerve is vulnerable to multiple forms of primary injury, which can result in traumatic optic neuropathy (TON). Multiple studies have shown that the optic tract may also be injured during TBI, though data regarding the temporospatial resolution of injury to the optic nerve are sparse. We evaluated the time course of optic nerve injury and visual impairments in our closed head impact acceleration mouse model of mild TBI (mTBI) designed to mimic repetitive injuries experienced in the context of sport. Our results show that inflammation and gliosis occur acutely in response to injury. Additionally, indications of optic nerve degeneration and functional loss of vision beginning at 1-month postinjury, and retinal ganglion cell loss at 7 months, revealed that the degeneration is continuous and permanent. Together, this study demonstrated that the optic nerve is vulnerable to damage during mTBI, which can cause TON and vision loss. These findings will be important for clinicians to consider to determine whether optic nerve is injured in the TBI patients with vision problems.